Development of Big Book Media Based on Riau Local Wisdom for Beginning Reading for Elementary School Students - Khofifah, Siti; Rahmi, Laili (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2024)
By having the ability to read and write, a person can live his life with better quality. Especially in an increasingly advanced era 21. Low interest in reading is the main factor in students' low reading skills. This research aims to develop big book media based on local Riau wisdom for beginning reading. The development model used is the 4D model, namely define, design, development. The data sources in this research are teachers, students, and validators, material experts, language experts, and design experts. The big book media is said to be suitable without revision according to the results obtained, namely the material aspect obtained a percentage of 92.5% in the very valid category, the language aspect 95% in the very valid category and the design aspect 96.25% in the very valid category. Overall the validity of the big book media obtained an average score of 94.58% so that this big book media is categorized as very valid without revision and is suitable for use. Then obtained student responses with an average of 96.6%. The implications of this big book media are expected to attract students to read, improve initial reading skills in lower grades, and increase students' knowledge about local Riau wisdom, specifically folklore.